Guidance and Counselling Programme and Overall Adjustment of Teenage Mothers: Evidence from Secondary Schools in Kenya - Opondo, Chirstian M.; Aloka, Peter Jairo O. (The Open Psychology Journal, 2020)
Background: School adjustment is multifaceted that involves an array of demands varying in kind and degree which requires a variety of coping responses. Several teen mothers have been re-admitted to secondary schools in Kenya. Objective: The present study investigated the Guidance and Counselling Programme and Adjustment of Teenage Mothers in Secondary Schools in Kenya .Methods: The study adopted ex post facto’s Causal-comparative research design. The target population of the study was 242 re-admitted teenage mothers from selected schools in Ugenya Sub County, Kenya. The sample size comprised of 138 re-admitted teenage mothers who underwent the counselling programme and 104 re-admitted teenage mothers who were integrated back to the school without going through the counselling gprogramme. Academic adjustment Questionnaire, Social Adjustment Questionnaire, Emotional Adjustment Questionnaire, Psychological Adjustment Questionnaire, Attitude towards Guidance and Counselling Questionnaire were used to collect data. The questionnaires had a good internal consistency of minimum α = 0.78. The data were analysed by both descriptive statistics such as frequency counts, standard deviation and percentages, and inferential statistics such as multiple regression techniques. Results: The results of the study revealed that student mothers registered the highest rating in social adjustment and they recorded the least rating in academic adjustment. However, the findings of the study revealed that students who had gone through formal counselling generally registered higher adjustments than those who did not pass through formal counseling. The teenage mothers’ attitude had a mediating effect on the relationship between guidance and counselling program and the overall adjustment of teenage mothers. Conclusion: School principals should provide comprehensive guidance and counselling programs to ensure the holistic adjustment of teenage mothers in schools.
Keywords: Guidance; Counselling program; Adjustment; Teenage mothers; Secondary schools; Kenya